A CYTOCHEMICAL DESCRIPTION OF THE MULTIPLICATION OF MENGOVIRUS IN L-929 CELLS - Franklin, Richard M. (The Rockefeller University Press, 1962)
A correlation of cytochemical changes with virus production has been studied in L cells infected with Mengovirus. After a latent period of about 2 hours, virus was produced rapidly, reaching maximum titers of up to 12,000 particles per cell in 6 to 8 hours. The earliest cytological change was in the nucleus and consisted of a slight condensation of chromatin. There is no evidence, however, for the multiplication of either the viral RNA or protein in the nucleus. RNA, of high molecular weight, accumulated in the perinuclear area of the cytoplasm and was later found in inclusions. The perinuclear RNA was digestible with RNase and may be located in or on ribosomes. The inclusion RNA was resistant to RNase but could be removed by pepsin or potassium permanganate; it is probably in completed virus particles. Viral antigen was first observed in a perinuclear location and later in the above-mentioned inclusions. Although the viral protein contains appreciable amounts of arginine and lysine, it is not a basic protein of the histone type. Phase-contrast microscopy of living cells clearly demonstrated the role of the inclusions in release of virus from infected cells. A comparison is made between these cytological changes in Mengo-infected cells and those which have been found by other workers in polio-infected cells. There are many very similar changes.